Parasitism interacts with mutual interference to limit foraging efficiency in larvae of Nephus includens (Coleoptera: Coccinellidae) - Bayoumy, Mohamed H.; Michaud, J. P. (My University, 2012)
Predator parasitism can modify predator–prey interactions through long-term (numerical) and short-term (functional response) impacts. However, mutual interference is another density-dependent factor that may affect predator foraging efficiency in the presence or absence of parasitism. This study examined the effects of parasitism of the invader Nephus includens (Kirsch) (Coleoptera: Coccinellidae) by Homalotylus flaminius Dalman (Hymenoptera: Encyrtidae), predator density, and prey density on the searching efficiency (a measure of area of discovery) using the cotton aphid, Aphis gossypii Glover (Hemiptera: Aphididae) as prey. Mutual interference reduced foraging efficiency by 47% in parasitized fourth-instar larvae compared to 44% in those unparasitized. Increasing predator density decreased searching efficiency more markedly in parasitized than in unparasitized larvae. The combined effects of parasitism and mutual interference reduced searching efficiency by 91%. Conversely, prey consumption by parasitized fourth-instar larvae increased with increasing prey density. Interference values declined from 0.98 to 0.82 with increasing prey density, indicating that the negative effect of parasitism on predator foraging diminished with increasing prey availability. Thus, these results support the inference of the ‘enemy release’ hypothesis, that invading predators may be more successful and have higher impacts on prey when they escape from parasitism. In the context of augmentation of N. includens against A. gossypii on guava in Egypt, releases of predator life stages immune to parasitism by H. flaminius (e.g., pupae or adults) in a suitable predator-prey ratio should minimize the negative effects of parasitism and intraspecific interference, and thus maximize efficiency of the predator against the pest.
Citation: Bayoumy, M. H., & Michaud, J. P. (2012). Parasitism interacts with mutual interference to limit foraging efficiency in larvae of Nephus includens (Coleoptera: Coccinellidae). Retrieved from http://krex.ksu.edu
Keywords: Area of discovery; Functional response; Homalotylus flaminius; Intraspecific competition; Predation; Searching efficiency